Sports Education in Senior High Schools: Analysis of Educational Technology Learning (ETL) During Covid-19 - Ade Rahmat; Iskandar Iskandar (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2022)
The purpose of the study. to analyze the factors that affect the learning outcomes of Physical Education, Sports, and Health of class XI students at Senior High School. there are three factors that can affect the learning outcomes of Physical Education, Sports and Health, namely factors contained within students (internal factors), factors that come from outside (external factors) and factors from the learning approach of the students themselves. Materials and methods. The population of this research is class XI State Senior High School. Qualitative descriptive analysis study using data collection techniques and instruments, namely documentation techniques and questionnaire techniques with randomly selected samples. Results. Based on the research results, internal and external factors often affect the learning outcomes of Physical Education, Sports and Health. Conclusions. internal and external factors often affect learning outcomes in Physical Education, Sports and Health. Likewise, the learning approach factors classified as sometimes affect the learning outcomes of Physical Education, Sports and Health.